Increased Serum Hepcidin Levels in Children and Adolescents with Attention Deficit Hyperactivity Disorder - Yazici, Kemal Utku; Yazici, Ipek Percinel; Ustundag, Bilal (Korean Coll Neuropsychopharmacology, 2019)
Objective: In this study, we aimed to evaluate the serum hepcidin levels in attention deficit hyperactivity disorder (ADHD) patients that were newly diagnosed with no history of psychotropic drugs. Methods: A total of 70 ADHD patients and 69 healthy controls were enrolled in our study. During the diagnosis, the Schedule for Affective Disorders and Schizophrenia for School-Age Children-Present and Lifetime version were applied. The sociodemographic data form, Turgay DSM-IV-Based Child and Adolescent Behavior Disorders Screening and Rating Scale, and Conners' Rating Scales-Revised: Long Form were used for the clinical evaluation. Serum hepcidin levels were measured and compared between the groups. Results: No significant difference between the groups in terms of age (p=0.533) and gender (p=0.397) was determined. In addition, the groups did not differ significantly for the other sociodemographic variables recorded. Serum hepcidin levels were found to be significantly higher in the patients with ADHD than healthy controls (p=0.019). Conclusion: To the best of our knowledge, this study is the first to evaluate the total serum hepcidin levels in ADHD patients. Our study findings may suggest that high levels of hepcidin may cause iron dysregulation in ADHD patients. However, further studies are required to establish a definite conclusion.
Keywords: Adolescent; Attention deficit disorder with hyperactivity; Child; Hepcidins; Iron